81‐3: Distinguished Paper: Developing High Efficiency Heavy Metal Free QD‐LEDs for Next Generation Displays. Issue 1 (29th May 2019) - Ippen, Christian; Guo, Wenzhuo; Zehnder, Don; Kim, Daekyoung; Manders, Jesse; Barrera, Diego; Newmeyer, Benjamin; Hamilton, Dylan; Wang, Chunming (Kevin); Hotz, Charlie; Ma, Ruiqing; Bin, Jong-Kwan; et al.
Abstract : In this paper we report on our progress on developing heavy metal free (or Cd‐free) QD‐LEDs for all three colors. With improvement in synthesis we have developed high quantum yield heavy metal free QDs (>95% for Red and Green; >80% for Blue) with peak wavelengths suitable for BT.2020. Building upon these high performance QDs and through novel device structure design and optimization we have demonstrated high efficiency heavy metal free QD‐LEDs with EQE=16.9%, 13%, 9% for Red, Green, Blue, respectively.